Strategies in developing tropical maize hybrids. - Vasal, S. K. (1994)
The strategies in a hybrid development program should be so oriented to achieve short, medium and long term objectives. The germplasm source utilized is quite important and should possess desirable agronomic traits with good plant and ear height characteristics along with good stalk quality to allow development of good progenitors. To achieve these objectives, it is imperative to introduce new strategies and modifications in the conventional systems to obtain higher efficiency. In this presentation various aspects are discussed relating to germplasm source oriented towards hybrids, integration and introduction of new schemes of population improvement parallel to hybrid development, production of vigorous and productive lines using diversified and efficient strategies, precise characterization of lines in inbred-line evaluation trials, combining ability in crosses with testers, identification of new hybrids during various stages of hybrid development, prediction of new hybrids with less number of single crosses, use of inbred lines in forming new populations as well as heterotic groups and synthetics. Options for developing single cross hybrids to add efficiency in the future are discussed.